A Case Series of Extrapulmonary Mycobacterium in Liver Transplant Recipients. Issue 5 (14th May 2021) - Lamm, Kevin; Jacobs, Carl; Russo, Mark W.
ABSTRACT: Liver transplant recipients are at increased risk of infection because of the immunosuppression required after transplantation. Infection by Mycobacterium species increases the morbidity and mortality of liver transplant recipients. The prompt recognition and diagnosis of opportunistic infection is necessary for good outcomes, particularly during periods of increased immunosuppression. The balance of immunosuppressive therapies during prolonged treatment with hepatotoxic medications has not been well studied and should be tailored for the unique clinical setting of each patient. The goal of treatment in these patients is to eradicate the disease and preserve allograft function.